2015
DOI: 10.1007/s00508-015-0702-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cataract surgery on macular thickness: a 6-month follow-up

Abstract: Findings confirmed the reversibility of macular thickness changes 6 months after cataract surgery and its return to preoperative values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Šiško et al [ 9 ] reported highest retinal thickness in the ETDRS grid areas one month after uncomplicated cataract surgery. They also stated mild decreasing trend in the measurements from the first month to the sixth month, without reaching preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…Šiško et al [ 9 ] reported highest retinal thickness in the ETDRS grid areas one month after uncomplicated cataract surgery. They also stated mild decreasing trend in the measurements from the first month to the sixth month, without reaching preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that macular or retinal thickness increased after cataract surgery [9]. Choroid was a vascular structure in close relation to the retina in the eye, and changes in choroid thickness might also be predicted.…”
Section: Introductionmentioning
confidence: 99%
“…However, they observed a slight downward trend in size from 1st to 6th month, without reaching the preoperative level. 14 This finding contrasts with the majority of studies reporting an increase in postoperatively macular thickness. 15 A study by Garbia et al observed significantly increase in postoperatively macular thickness for 6 months.…”
Section: Discussionmentioning
confidence: 82%